Experimentación con técnicas artesanales de tintura textil del pueblo Salasaka - Aldas Arroba Paola Jazmín (2024)
The main objective of this thesis project is to revalue the artisanal textile dyeing techniques of the Salasaka people, which have been taught for years thanks to the community's artisans, through these artisanal dyeing methods they express identity and heritage. culture that characterizes them. Thus seeking to preserve these techniques that have been a source of employment for generations. The artisanal techniques reflect the community's extensive cultural heritage and deep appreciation for the natural environment. These techniques involve processes that involve the extraction of plants, minerals, fruits and other organic resources, in such a way that each part of the process is carried out by hand, which is why they are highly valued inside and outside the community. The Salasakas have a wide variety of traditional dyeing designs that reflect their culture and tradition, as well as express their skills and abilities. For this reason, this project proposes the development of a textile catalog where various artisanal dyeing techniques are integrated, where creativity and innovation are demonstrated. In addition, we seek to continue keeping the characteristic tradition of Salasaka alive, providing a sustainable and environmentally friendly alternative.